Effect of High Temperature on Compressive Strength of Concrete Prepared Using Different Types of Aggregates - Ay, Serhay; Demi̇rel, Bahar; Tuğla, Ruki̇ye; Yazicioğlu, Sali̇h (Springer International Publishing, 2018)
Concrete is a building material commonly used in the construction structures. There are many reasons why concrete is preferred. One of these reasons is fire resistance of concrete. Concrete is not a combustible material, but it behaves differently under high temperature. Aggregates constitute an important part of concrete volume. Differences in aggregate properties significantly affect the performance of the concrete during heating. Differences in these properties also cause cracks and breakages in parts of the concrete and significant losses in adherence. When we look at these effects, we have seen that high temperature creates a threatening environment for concrete. Therefore, it is necessary to investigate the behavior of the concrete caused by the high temperature. In this study, we investigated the effect of high temperature on the compressive strength of concrete specimens prepared using different aggregate types. For this purpose, 10 × 10 × 10 cm and 15 × 15 × 15 cm cube samples were prepared by using CEM I 42,5 (N) type Portland Cement and two different types of aggregates (basaltic crushed stone, stream aggregate). The Concrete produced using basalt crushed stone is coded as “BCC” and the concrete produced using the stream aggregate is coded as “SAC”. These concrete specimens were tested at room temperature and high temperature (300, 600 and 900 °C) after 28 days. We used the remaining samples at room temperature as control samples. We tested the compressive strength on all concrete samples. We studied the relationship between the compressive strength results and the concrete mass size. As a result of this study, it was found that the compressive strength of BCC is higher than SAC. When the relationship between the strength values of the concrete with high temperature effect and the concrete sample size was examined, it was found that the temperature affected the center of the small concrete samples more quickly. The resulting data showed that the 10 × 10 × 10 cm size concretes have low compressive strength.